Significant Role of Professional Development Center in Healthcare Setup in the Provision of Quality Education, Advance Learning and Patient Care - Anwar, Adina; Irfan, Muhammad; Kazi, Sarah; Khan, Erum; Fatima, Mehwish; Kabir, Varisha (Pakistan Armed Forces Medical Journal, 2023)
Objective: To define the significant role of Professional Development Center (PDC) at Dow University of Health Sciences in provision of quality education, learning and patient care.Study Design: Retrospective cohort study.Place and Duration of study: Professional Development Center, Dow University of Health Sciences, Karachi Pakistan, from 2018 to 2022.Methodology: Study was conducted through non-probability convenience sampling technique to include all CME workshops and seminar records of PDC. Further feedback forms were also collected from the participants after each training session to analyze their feedbacks.Results: As per the five year, records a total of 728 CME workshops and 635 CME seminars were conducted by PDC from the 2018 to Feb 2023. Major focus areas of the CME lectures and workshops was Medicine and Allied Health sciences, continuously for the last five years. However, when major focus area of CME workshops was assessed it was that they were mainly related to basic life support where, most of the workshops were conducted to train the students of Dow Institute of Medical Technology. When participants’ feedback was taken regarding the organization and impact of workshop, it was found that most of them agreed that handouts were helpful (77.25%) and questions were adequately responded (77.25%), respectively.Conclusion: It was found that PDC significantly played its role in enhancing knowledge and skills of the healthcare professionals in healthcare setup, thereby providing quality education, learning and patient care.